Analysis of soil microbial diversity of Miscanthus lutarioriparius communities in different areas of Dongting Lake - Yu, Zixuan; Zhu, Peng; Li, Bo; Qian, Hong-Ge; Hu, Qingqing; Yang, Sai (Frontiers in Environmental Science, 2026)
Miscanthus lutarioriparius communities are a crucial component of the Dongting Lake wetland ecosystem. To understand how habitat heterogeneity shapes their associated soil microbiome, this study investigated the spatial patterns of bacterial and fungal diversity across seven regions using high-throughput sequencing of 16S rRNA and ITS genes alongside soil physicochemical analyses. Our results revealed distinct assembly mechanisms for bacteria and fungi. Bacterial community composition and alpha diversity exhibited significant spatial heterogeneity, primarily correlated with altitude, pH, and ammonium nitrogen. In contrast, fungal communities were more homogeneous in composition, with their alpha diversity strongly linked to soil total phosphorus. Distance-based redundancy analysis confirmed that bacterial communities were mainly structured by abiotic factors (altitude, pH), whereas fungal communities were predominantly shaped by nutrient availability (total phosphorus, total nitrogen, soil organic matter, and total potassium). Co-occurrence network analysis indicated a modular structure with stronger intra-than inter-domain connections, dominated by saprotrophic Ascomycota hubs. Functional prediction further supported these trends, revealing a prevalence of biofilm-forming bacteria and site-specific saprotrophic fungal guilds. This study demonstrates that bacterial and fungal communities in M. lutarioriparius wetlands are filtered by fundamentally different environmental factors—altitude and related abiotic conditions versus soil nutrient availability. These findings provide a clear ecological framework for understanding microbial biogeography in dynamic wetlands and underscore the need to consider domain-specific responses in conservation and restoration strategies.